Non-conservative Behavior of Dissolved Organic Matter and Trace Metals (Mn, Fe, Ba) Driven by Porewater Exchange in a Subtropical Mangrove-Estuary - Mori, Corinna; Santos, Isaac R.; Brumsack, Hans-Jürgen; Schnetger, Bernhard; Dittmar, Thorsten; Seidel, Michael (Frontiers in Marine Science, 2019)
Estuaries play a key role in controlling the land-ocean fluxes of dissolved organic matter (DOM), nutrients and trace metals. Here, we study how mangrove-fringed areas affect the molecular DOM and trace metal composition in a subtropical estuary. We combined molecular analysis of solid-phase extractable (SPE) DOM using ultrahigh-resolution mass spectrometry with organic and inorganic bulk parameter analyses in surface and porewater along the estuarine gradient of a mangrove-fringed estuary in Australia (Coffs Creek). Statistical analysis and mixing models demonstrate that the fluvial and mangrove-porewater derived DOM and inorganic chemical species were altered and/or removed by the estuarine filter before reaching the coastal ocean. The mangrove-fringed central estuary was a net source for dissolved Mn and Ba as well as total dissolved nitrogen (TDN) and dissolved organic carbon (DOC) to the tidal creek, likely due to the exchange of mangrove-porewater strongly enriched in these constituents. Dissolved Fe was removed from the water column, probably during the tide-driven circulation of creek water through the sulfidic mangrove sediments. In the mangrove-porewater dominated tidal creek, sulfur- and nitrogen-containing as well as aromatic DOM compounds were relatively enriched, whereas phosphorous-containing DOM was relatively depleted compared to non-mangrove fringed areas. In areas with intense mixing of estuarine and marine water masses we observed a strong decrease of these DOM compounds relative to values expected from conservative mixing, suggesting their removal by photodegradation and co-precipitation with particles such as Mn(hydr)oxides and/or as organometallic complexes, leading to more aliphatic DOM signatures at the creek-mouth. Tidally driven porewater exchange and surface water runoff from the mangroves had a stronger effect on the biogeochemical cycling in the estuary than the fluvial input during a dry compared to a wet season. Our study confirms that mangroves can significantly contribute to biogeochemical budgets of (sub)tropical estuaries.